2016
DOI: 10.1007/s10571-016-0459-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Metformin Attenuates Cognitive Impairments in Hypoxia–Ischemia Neonatal Rats via Improving Remyelination

Abstract: Perinatal hypoxia-ischemia (H/I) causes brain injury and myelination damage. Finding efficient methods to restore myelination is critical for the recovery of brain impairments. By applying an H/I rat model, we demonstrate that metformin (Met) treatment significantly ameliorates the loss of locomotor activity and cognition of H/I rat in the Morris water maze and open field task tests. After administration of Met to H/I rat, the proliferation of Olig2+ oligodendrocyte progenitor cells and the expression of myeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…It has been inferred that early intervention is important to prevent and correct the pathological phenotypes of neurodevelopmental disorders, thereby reversing behavioral and functional deficits in adults (Cioni et al, 2016 ). Treatment with Metformin significantly improved deficits of locomotor activity and cognition in rats subjected to perinatal hypoxia-ischemia (Qi et al, 2017 ). Another study indicated that metformin administration during the neonatal period could alleviate a contextual fear memory deficit in a fetal alcohol spectrum disorder model (Tunc-Ozcan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been inferred that early intervention is important to prevent and correct the pathological phenotypes of neurodevelopmental disorders, thereby reversing behavioral and functional deficits in adults (Cioni et al, 2016 ). Treatment with Metformin significantly improved deficits of locomotor activity and cognition in rats subjected to perinatal hypoxia-ischemia (Qi et al, 2017 ). Another study indicated that metformin administration during the neonatal period could alleviate a contextual fear memory deficit in a fetal alcohol spectrum disorder model (Tunc-Ozcan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been illustrated that metformin can promote neurogenesis and protect BBB integrity in experimental stroke [ 26 , 27 ]. Additionally, metformin has been identified to ameliorate cognitive impairments via improve remyelination in a neonatal white matter injury paradigm [ 28 ]. However, to the best of our knowledge, few studies have reported that treatment with metformin is able to promote neurogenesis and preserve BBB integrity in an animal model of neonatal HI brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Drug delivery properties, dosage and use can also be complex to translate from a adult to neonatal setting. Several proof-of-concept studies with different classes of diabetes drugs as a treatment in neonatal HIE have been identified with glibenclamide (Zhou et al, 2009), metformin (Dadwal et al, 2015;Fang et al, 2017;Qi et al, 2017) and exendin-4 (Rocha-Ferreira et al, 2018). These diabetes drugs act on a plethora of biological pathways (Rosa et al, 2008;Zhang et al, 2016;Zhu et al, 2016) and the precise mechanisms of action of diabetes drugs for neuroprotection are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its neuroprotective effects, metformin has been shown to promote neurogenesis by enhancing neural precursor selfrenewal, proliferation, and differentiation (Potts and Lim, 2012;Wang J. et al, 2012). Increased neurogenesis upon metformin treatment resulted in improved memory formation in multiple experimental models of brain injury (Jin et al, 2014;Liu et al, 2014;Dadwal et al, 2015;Ge et al, 2017;Qi et al, 2017). In vitro studies using the OGD model demonstrated that metformin improves neuronal viability and regulates programmed cell death in a caspase-independent manner, thereby reducing ischemic reperfusion injuries (Mielke et al, 2006;Meng et al, 2016;Gabryel and Liber, 2018;Mohammad Alizadeh et al, 2018).…”
Section: Metforminmentioning
confidence: 99%
See 1 more Smart Citation